2020
DOI: 10.1093/eurpub/ckaa165.476
|View full text |Cite
|
Sign up to set email alerts
|

Charting mandatory vaccination policies worldwide

Abstract: Background Mandatory vaccination is becoming an increasingly important policy intervention for governments trying to address low vaccination rates. However, the evidence about which countries have mandatory vaccination policy worldwide and discussions surrounding their impact has largely been limited to high-income countries. While many recent publications discuss the issue, none provide a comprehensive list. This is an obvious gap in the discussion about the merits of introducing mandatory v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Communicating such research on the efficacy of vaccines is in turn essential for building public trust and reducing vaccine hesitancy. 21,22 Kreps et al (2021) found that perceived vaccine efficacy was the strongest predictor of COVID-19 vaccine uptake in the United States. 23 Sherman et al (2021) studied people's willingness to be vaccinated against COVID-19 and their attitude towards vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Communicating such research on the efficacy of vaccines is in turn essential for building public trust and reducing vaccine hesitancy. 21,22 Kreps et al (2021) found that perceived vaccine efficacy was the strongest predictor of COVID-19 vaccine uptake in the United States. 23 Sherman et al (2021) studied people's willingness to be vaccinated against COVID-19 and their attitude towards vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…People with access to better health services, which themselves lead to better health outcomes, and people from the European region are those that least agree that vaccines are important for children. 10,39 The Strategic Advisory Group of Experts working group on vaccine hesitancy suggests 3 main strategies to address vaccine hesitancy: understand its root causes, engage civil society and other partners to support immunization, and develop and promote tools to address vaccine hesitancy. 40 It is very important to account for particularities in each country when evaluating and addressing vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization coverage for all of the childhood vaccines in these countries was >90%. The largest differences were seen with measles vaccine coverage, which ranged from 90% in Canada and the USA, to 95% in Australia and the UK (Vanderslott et al, 2013).…”
Section: Resultsmentioning
confidence: 99%